2004
DOI: 10.1093/ajcn/79.6.1013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of self-reported with objectively assessed energy expenditure in black and white women before and after weight loss

Abstract: Premenopausal women overestimate PA estimates on questionnaires. Overestimation of PA in weight-reduced black women is greater than in weight-reduced white women and never-overweight black and white women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 30 publications
3
70
1
Order By: Relevance
“…18,19 A Bland-Altman analysis 26 indicated that the heart rate monitor provided reasonable group estimates of ExEE relative to indirect calorimetry, although error was evident at the individual level, a finding that is consistent with other heart rate monitors previously investigated in our laboratory (unpublished data). The implication of this finding is that researchers using heart rate monitors for large-scale lifestyle interventions can rely on the ExEE estimates made by the heart rate monitors.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…18,19 A Bland-Altman analysis 26 indicated that the heart rate monitor provided reasonable group estimates of ExEE relative to indirect calorimetry, although error was evident at the individual level, a finding that is consistent with other heart rate monitors previously investigated in our laboratory (unpublished data). The implication of this finding is that researchers using heart rate monitors for large-scale lifestyle interventions can rely on the ExEE estimates made by the heart rate monitors.…”
Section: Discussionsupporting
confidence: 76%
“…15 Self-reported exercise diaries and questionnaires have been used in the past to measure adherence; 9,16,17 however, overestimation of self-reported exercise data has been identified as a problem, particularly in overweight and obese individuals. 18,19 Support for the use of objective measures of diet and exercise is increasing; 20 a change that is required to elucidate which treatment component is not being followed and to what extent this is contributing to a lack of expected change in both weight loss 21 and health benefit.…”
Section: Introductionmentioning
confidence: 99%
“…The more objective measures (pedometer, BMI, and waist measurement) were consistent with the marked dyslipidemia and higher blood pressure found in the type 2 diabetic cohort. These reporting errors are consistent with prior research (23)(24)(25). Underreporting of caloric intake may be due to inattention to, or lack of knowledge of, healthy foods and portion size (26), both of which can negatively impact achievement of carbohydratecounting proficiency.…”
supporting
confidence: 86%
“…FEE was underestimated by 14.6% relative to DEE, but this was improved to 5.1% (P ¼ 0.071) when FEE was adjusted for EPOC and TEF. Some studies have also found factorial underestimation of daily EE (Haggarty et al, 1994;Leonard et al, 1997), but others have reported overestimation (Alfonzo-Gonzalez et al, 2004;Walsh et al, 2004), or no difference between FEE and DEE measures (Bratteby et al, 1997;Jones et al, 1997;Morio et al, 1997;Withers et al, 1998;Seale et al, 2002). Such discrepancies are very likely owing to differences in methods used to determine BMR and energy costs of activities, the number of activity categories used and the accuracy of estimates or records of time spent in activities, all of which affect the precision of factorial methods.…”
Section: Resultsmentioning
confidence: 99%